2017
DOI: 10.1042/bsr20160268
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the association of serum ischaemia-modified albumin levels with human hypothyroidism and hyperthyroidism

Abstract: Serum levels of ischaemia-modified albumin (IMA) have been studied as a novel and simple measure of oxidative stress (OXS) in different thyroid pathologies. However, results of available studies in the literature were not consistent. This meta-analysis was attempted to quantify the overall effect size for serum IMA levels in human hypothyroidism (HT) and hyperthyroidism (HYT) and to study its associations with the thyroid profile. Databases of PubMed/Medline, EMBASE, Google Scholar, Web of Science and Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…IMA has been proposed as an early biomarker for various diseases associated with ischemia and oxidative stress, including myocardial infarction and cerebrovascular accidents, diabetes mellitus and renal failure, and hypothyroidism and hyperthyroidism [21,23,42,66]. Mounting experimental data suggest that this marker is ambiguous and that its values depend on the type and stage of the pathological process and methods used.…”
Section: іма As a Marker For Diseasesmentioning
confidence: 99%
“…IMA has been proposed as an early biomarker for various diseases associated with ischemia and oxidative stress, including myocardial infarction and cerebrovascular accidents, diabetes mellitus and renal failure, and hypothyroidism and hyperthyroidism [21,23,42,66]. Mounting experimental data suggest that this marker is ambiguous and that its values depend on the type and stage of the pathological process and methods used.…”
Section: іма As a Marker For Diseasesmentioning
confidence: 99%
“…Thyroid hormones play a role in regulating mitochondrial respiration and oxidative metabolism, affecting free radical production and OS. Accelerated basal metabolic rate and oxidative metabolism in hyperthyroidism lead to an increased free radical generation and OS (9). The literature re-fT3: Free triiodothyronine; fT4: Free thyroxine.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones have an essential role in regulating mitochondrial respiration and oxidative metabolism, which further affects oxidative stress (OS). Therefore, OS levels might be affected by variations in thyroid hormones (9). Previous studies have shown that high serum fT3 and fT4 stimulate free radicals in mitochondria and cause an increase in OS (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…While, as reported in many studies, IMA which is an indicator of ischemia and oxidative stress may increase especially in cardiac ischemia, it is understood from the literature that it may also increase in many noncardiac diseases [41,42]. Reddy VS et al identified the relationship between IMA and thyroid diseases in a meta-analysis and they reported that IMA values increase in both hypothyroidism and hyperthyroidism and can be easily measured as an oxidative stress parameter in thyroid dysfunctions [43]. In our study results, it was seen that Vit C support was not able to prevent IMA formation.…”
Section: Discussionmentioning
confidence: 99%